From diluted solid solutions to high entropy alloys: Saturation grain size and mechanical properties after high pressure torsion. (February 2021) - Keil, Tom; Bruder, Enrico; Laurent-Brocq, Mathilde; Durst, Karsten
Abstract: Effects of solutes on saturation grain size and mechanical properties are investigated for the Cantor alloy and Ni-enriched variations ((CrMnFeCo)x Ni1-x ) with x=0.8, 0.4, 0.08 and 0. Indentation on coarse-grained and severely deformed states shows increasing hardness with increasing alloying content due to higher solid solution strengthening and Hall-Petch contributions. Nanoindentation strain rate jump tests reveal similar rate sensitivities of the deformed states without pronounced transient regimes. All compositions exhibit a history dependent softening indicating an unstable microstructure. The saturation grain size ds after HPT deformation inversely correlates with the solid solution strengthening contribution, i.e. the higher Δτ the lower ds . Graphical abstract: Image, graphical abstract